2013
DOI: 10.1523/jneurosci.0631-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous EEG and fMRI Reveals a Causally Connected Subcortical-Cortical Network during Reward Anticipation

Abstract: Electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) have been used to study the neural correlates of reward anticipation, but the interrelation of EEG and fMRI measures remains unknown. The goal of the present study was to investigate this relationship in response to a well established reward anticipation paradigm using simultaneous EEG-fMRI recording in healthy human subjects. Analysis of causal interactions between the thalamus (THAL), ventral-striatum (VS), and supplementary motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 67 publications
5
56
1
1
Order By: Relevance
“…Previous results using this paradigm have shown reliable and robust activation of the VS [55]. The task requires a fast button press directly after a flash target following a reward anticipation cue to win a potential reward.…”
Section: Methodsmentioning
confidence: 98%
“…Previous results using this paradigm have shown reliable and robust activation of the VS [55]. The task requires a fast button press directly after a flash target following a reward anticipation cue to win a potential reward.…”
Section: Methodsmentioning
confidence: 98%
“…Simultaneous EEG-fMRI imaging findings during reward anticipation in fact demonstrated that negative SCPs (CNV activity) correlated with cortical and subcortical reward system activation. 61 Evidence to support this prediction in ADHD is still limited, but preliminary results of an ongoing study seem to point in this direction. 62 Although participants with ADHD showed a significant hypoactivation in the neural reward pathway before training compared with healthy controls, 20 sessions of SCP-neurofeedback led to a modification and partial functional normalization in pivotal reward-related structures.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Alarmingly, the presented pattern of spurious motion related EEG-BOLD effects was found employing preprocessing steps and analysis steps commonly employed in EEG-fMRI (Baumeister et al, 2014;de Munck et al, 2007;de Munck et al, 2009;Debener et al, 2007;Hanslmayr et al, 2013;Hanslmayr et al, 2011;Jann et al, 2009;Jansen et al, 2012;Laufs et al, 2006b;Laufs et al, 2003;Li et al, 2012;Liu et al, 2012b;Mayhew et al, 2010;Mayhew et al, 2012;Mayhew et al, 2013;Meyer et al, 2013;Novitskiy et al, 2011;Plichta et al, 2013;Regenbogen et al, 2012;White et al, 2013) and could easily pass as neurophysiological plausible results. The relationship of theta oscillatory power and successful memory formation remains controversial, as opposing effects have been reported by recent studies (Hanslmayr and Staudigl, 2014).…”
Section: Motion Causes Seemingly Neurophysiological Plausible Effectsmentioning
confidence: 99%